Sandwich thoracic branch endoprosthesis technique for endovascular repair of thoracic aortic aneurysm with aberrant right subclavian artery - Yasmeen Dhindsa, MD; Alexander DiBartolomeo, MD; Gregory A. Magee, MD, MSc; Fernando Fleischman, MD; Sukgu M. Han, MD, MS (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
Subclavian artery coverage is frequently required to achieve an adequate proximal seal during thoracic endovascular aortic repair. The thoracic branch endoprosthesis (TBE; W.L. Gore & Associates) is the first U.S. Food and Drug Administration–approved branched device for thoracic endovascular aortic repair, designed for left subclavian artery incorporation. However, anatomic suitability of the TBE has been shown to be limited. In the present report, we describe a novel technique using the TBE in a sandwich periscope configuration to allow for emergent repair of a ruptured thoracic aortic aneurysm with a highly angulated proximal seal zone and aberrant right subclavian artery.